Study on drivers’ behaviour relationships to reduce road accidents in Puchong, Selangor Darul Ehsan - Amiruddin Ismail; Gan, Soon Yi; Mohd Kamarul Ifzam Mohd Zain (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
Road accidents are the most common phenomenon in our daily life which occurs in every part of the world. In Malaysia, these issues took away many precious lives despite causing problems to the living family. Based on the Global Status Report, World Health Organisation (WHO) on Road Safety, Malaysian road users are categorized as the worst in South East Asia with an average of 23.8 deaths per 100,000 populations. One of the main factors that contribute the issue is drivers’ behaviour. Moreover, this study was conducted to investigate the relationship between drivers’ attitude towards road accidents in urban areas. Puchong in Selangor was selected and identifi ed to have numerous cases of road accidents. Descriptive data of road accidents in Puchong were analysed to gain the results in graphical and numerical form. The causes of road accident due to driving’s behaviour were verifi ed through the developed drivers’ behaviour model. A related suggestion has been stated based on this study to reduce and prevent the road accident at the studied area.